Value management in building construction industry of northern cyprus: Addressing a theory and practice gap - Afsharghotli, Alireza; Rezaei, Alireza R. (My University, 2013)
Construction sector in Northern Cyprus (TRNC) proved its potential of being locomotive in the economy after 2005. Increasing expectations to solve Cyprus problem, the positive reflections of the Annan Plan and the hypothetical abundance of liquidity in the world caused the construction sector to play the leading role in the economy of TRNC. However, these conditions have been reversed in a negative way today. Furthermore, internal problems such as high production costs, lack of international workshops, absence of development plan, lack of internationally certified construction firms, weak institutional and financial structure of contractors, low level of Value Management (VM) awareness among related authorities and private sectors, absence of country physical plan and less number of VM practitioners and consultants combined with uncontrollable external factors create negative impact on the sector's productivity and hence the competitiveness of the building industry. The aim of this study is to review the gaps that exist, particularly on how VM is being practiced in to comparison with the published VM body of knowledge. Therefore, the unclear description of current applications and the level of VM practice in the country were investigated. This research includes a comprehensive literature study, a structured questionnaire among construction management experts, interviews with building construction companies and related firms on the challenge of VM knowledge level and practice in building industry, analysis of this information to develop findings, and extending these to appraise the critical issues that could be targeted for building construction sector. The result of the survey, were further analyzed in details and guidelines were proposed to enhance an improved environment. Moreover, strategies were suggested to develop VM adoption and awareness level among construction industry practitioners in TRNC. © 2013 American Society of Civil Engineers.
2013 Architectural Engineering National Conference: Building Solutions for Architectural Engineering, AEI 2013 --
Keywords: Construction Industry; North Cyprus; Value Management